The Existence of Indonesian Islamic Market Stocks During The Covid-19 Pandemic - Pratiwi, Febryna Rizka; Fatwa, Nur, Dr. (UI Scholars Hub, 2022)
When the first Covid-19 case entered Indonesia, Jakarta Composite Index (JCI) underwent a very deep correction until it reached its lowest point in the last decade, from the level of 6,300 to the level of 3,975 as of March 24, 2020. But, an interesting fact in the following months the JCI consistently rose, and even managed to break back above the 6000 level in the period from the end of 2020 to the beginning of 2021. Indonesia has again won the nomination for the category 'The Best Islamic Capital Market 2020' from the Global Islamic Finance Awards (GIFA). The growth of the Islamic capital market during the pandemic was also influenced by the development of the Sharia Online Trading System. This study wants to explain the existence of the Indonesian Islamic capital market during the COVID-19 pandemic. This study uses a qualitative approach with descriptive analysis method. The result of this study is that Indonesian Islamic capital market managed to rise from the crisis slump at the beginning of the emergence of the first cases of Covid-19 entering Indonesia. This is shown by several important points, such as the increase in the number of Islamic stock investors which reached 25.2%, sharia market capitalization reaching 3,344.9 trillion rupiah and The value of outstanding sukuk through public offerings as of October 2021 reached Rp. 34.98 trillion, with the number of successful series issued as many as 186 series.